Development of a diagnostic system for the presence of rotor eccentricity in traction induction motors - Victor Yurchenko; Olena Nezlina; Valentyna Tkachenko (Збірник наукових праць Державного університету інфраструктури та технологій: серія "Транспортні системи і технології")
The aim of research is to develop a system for functional diagnostics of the presence of rotor eccentricity in traction induction motors of railway rolling stock. To achieve the aim, the following objectives were solved in the work: the Prony’s method was adapted to perform the task of diagnosing the eccentricity of the rotor of an induction motor during the operation of the rolling stock; the algorithm of functioning of the system of functional diagnosis of rotor eccentricity based on the adapted Prony’s method is proposed; a structural diagram of the rotor eccentricity diagnosis unit based on the adapted Prony’s method is proposed; a structural diagram of the system of functional diagnosis of rotor eccentricity is proposed. The most important results are obtaining a mathematical model of the Prony’s method, adapted to the task of diagnosing the eccentricity of the rotor of an induction motor during the operation of rolling stock. The adaptation of the Prony’s method algorithm is performed by applying the Wiener-Hopf procedure to the analyzed signals. This will make it possible to apply the proposed algorithm in conditions where the process of changing the analyzed signals is stochastic in nature. This will make it possible to determine the eccentricity degree of the AM rotor with greater accuracy and to make a more correct decision regarding the AM operation with the existing eccentricity of the rotor.